HADITHS ON THE PERSONALITY AND SPIRITUAL AND ETHICAL EDUCATION OF OUR PROPHET MUHAMMAD PBUH (World Bulletin of Social Sciences, 2023)
In this article, discussing the supernatural events that happened at the time of the birth of the Prophet Muhammad, peace and blessings of God be upon him, his unique qualities, historical and unique personality, the hadiths he narrated and the pedagogical-psychological features of the hadiths, we aim to make the whole generation spiritually rich and morally pure in the current process of globalization and integration. , hard-working, family-oriented, physically fit, loyal to the motherland, love for parents, wise-educated with independent opinion and position, selflessly working for the independence of our country and as a competitive staff, it is one of the main sources serving in education, both theoretical and practical aspects It was explained that the use of these scientific sources in the education of the mature generation is one of the current problems
Keywords: Rasuli Akram; guidance; hadith; science